Peningkatan Mutu Sumber Daya Manusia Lembaga Pendidikan Isalm Berbasis Sustainable Development Goals Di Yayasan Pendidikan Anak Saleh Kota Malang - Anwar Sa'dullah; Triyo Supriyatno (STAI Ma'had Aly Al-Hikam Malang, 2021)
The dynamics of the development of educational institutions in Indonesia cannot be stopped, let alone limit the rapid development of institutions. Not a few institutions have closed down due to the lack of interest in the community to send their children to school. The problem basically concerns the quality of the institution, especially human resources who play a role as the subject or manager of the institution. For quality institutions, it is certain that they will not be displaced by global developments and the demands of the community for quality education. The research method of this article is qualitative research with a descriptive analysis approach. This type of research is a case study with a multi-case design considering the choice of two research institutions even though one shelter, namely early childhood education and primary school Anak Saleh Malang City. The results showed that early childhood education has four strategies in improving the quality of human resources, including: training, professional development, career development, and performance appraisal. One of the four strategies has the theme of developing human resources through workshops on the responsibilities of employees in schools and families. Meanwhile, the Saleh Children Primary School has three strategies for developing human resources, namely: monitoring, evaluation and follow-up. Among the three strategies, one of the activity designs is the awarding of employees through employee and teacher months including the involvement of parents in follow-up programs. Keywords: Quality, Human Resources, SDGs, Saleh Children